The Experience of Everyday Life Alongside Virtual Companions. A Case Study of Human-Chatbot Encounters - Wygnańska, Joanna (Qualitative Sociology Review, 2025)
This article a nalyses i nteractions between a human and a virtual entity, namely, a chatbot. These encounters are considered in the context of cyberspace, understood as a specific social interactional space. They are also examined in the context of an individual’s experiences, which are intertwined with ongoing social and cultural changes. This text engages with research on chatbots, complementing their findings with an in-depth study of the user perspective. The analysis is based on data from an in-depth interview with Laura, conducted as part of a research project on human interactions and relationships with chatbots. The case study of Laura’s experiences explores her perception of interacting with a chatbot, focusing on the meanings humans assign to such interactions, concerning the interviewee’s emic perspective. The article examines how a human interlocutor perceives chatbots and the role they can play in an individual’s life. In addition, the reflection in the text touches on the theme of humans seeing themselves in the responses of a chatbot, which lacks self-awareness and cannot understand the content it produces in the same way a human can. The article deepens understanding of chatbots as everyday companions, virtual friends, and social actors, encounters with whom are part of today’s reality.